Fibrinolytic Activity in Blood Is Distributed over a Cellular and the Plasma Fraction which Can Be Modulated Separately - van Giezen, J J J; Chung-A-Hing, J E; Vegter, C B; Bouma, B N; Jansen, J W C M (Thrombosis and Haemostasis, 1994)
Blood fibrinolytic activity is mediated by plasma and cellular components. We have studied blood fibrinolytic activity in different species and investigated the distribution pattern in rats after modulation with PAF, dexamethasone, or retinoic acid. Whole blood and plasma activity were measured in an assay system using human or endogenous fibrin as substrate. When human fibrin was used as substrate marked species differences in distribution of fibrinolytic activity were observed. In rat and murine blood most fibrinolytic activity was associated with the plasma fraction (70% and 50% respectively) while in human and canine blood the plasma fraction contained only 30% of the blood fibrinolytic activity. When endogenous fibrin was used as substrate the distribution pattern of fibrinolytic activity in rat blood changed dramatically. Less than 25% of the blood fibrinolytic activity was now present in the plasma fraction.The fibrinolytic system was further investigated in rats using specific inhibitors of proteolytic activity. Blood fibrinolytic activity could be inhibited for 33% by antibodies raised against t-PA and 60% inhibition was obtained in the presence of amiloride. No significant effect of elas-tinal (an inhibitor of elastase) could be detected. Plasma fibrinolytic activity was not affected by these inhibitors. The fibrinolytic activity in plasma could be enhanced about 100-fold after i. v. PAF administration (10 μg/kg). This extra fibrinolytic activity could be fully blocked by antibodies raised against t-PA. Oral administration of dexamethasone or retinoic acid affected blood fibrinolytic activity by modulating selectively the activity mediated by the cellular fraction. Dexamethasone treatment (1 mg/kg) resulted in a 59% decrease of this fibrinolytic activity. Retinoic acid treatment (3 mg/kg) resulted in a 69% increase of the fibrinolytic activity in this phase. Both compounds affected selectively the t-PA activity.We conclude that 1) the plasma as well as the cellular fraction contribute to the blood fibrinolytic activity; 2) the plasma derived fibrinolytic activity as such is a minor part of the total whole blood fibrinolytic activity (the mouse is an exception); 3) the rat blood fibrinolytic activity is evoked by u-PA (two third) and t-PA (one third) mediated processes; 4) the blood fibrinolytic activity can be modulated, in contrast to the plasma activity as such, by retinoic acid or dexamethasone; 5) the plasma fibrinolytic activity is subject to modulation by compounds which evoke a direct PA increase.